The journey of Indonesian traditional medicine - Yunita, Fenny; Gunawan, Shirly; Silaban, Hertina; Chaidir (Fakultas Kedokteran Universitas Tarumanagara, 2024)
Indonesia is the second mega biodiversity country in the world, with more than 17.000 islands and 1.340 tribes with abundant potency in traditional medicine. Traditional medicine in Indonesia has a long history. It has been greatly influenced by foreign cultures, such as India (Ayurveda), China (Traditional Chinese Medicine), and the Middle East (Arabic/Islamic/Thibbun Nabawi). Traditional Indonesian medicine is also known as Jamu, which refers to prayer, physical and non-physical techniques, and herbal medicine that aims to maintain and improve health. Many national surveys have shown that Indonesian people strongly believe in traditional medicine and still use it daily. The development of traditional medicine in Indonesia started early in the 8th century, as shown in the reliefs of Borobudur and many other temples. The development of traditional medicine in Indonesia also refers to the WHO's traditional medicine strategy, which focuses on the 3Ps (Products, practices, practitioners). World Health Organization (WHO) recommends using traditional medicines to maintain public health, preventing and treating diseases, especially chronic and degenerative diseases. WHO also supports efforts to improve the safety and efficacy of traditional medicines. Traditional Indonesian medicine has great potential to help improve the community's health. Cross-sectoral cooperation from all sectors, such as academics, business, government, and the community, is needed to develop traditional Indonesian medicine and support its use in health service facilities towards independence in the health sector.